Peranan Kepuasan dalam Meningkatkan Loyalitas Pelanggan (Studi pada Pelanggan manfaat Atribut Produk Simpati) - Kezia Kurniawati; Kartika Imasari Tjiptodjojo (Universitas Kristen Maranatha, 2015)
Intermediate level consumers (churn) in the telecommunications industry were high currently, causing the company always strives to improve the quality, provide value, attract new customers and retain existing customers. Loyalty means consumers back to business transactions (purchases) repeatedly, although perhaps a product of the company is not the best product on the market or have the lowestprices. Consumer behavior can be explained by a view that customers are satisfied, generally will be loyal to the products offered and finally, the high level of satisfaction and loyalty of customers, will be able to reduce the level of chumhappened. This research uses sampling method is based on specific criteria or considerations, where the criteria or considerations used are user simPATIzone and a resident of the city of Bandung. This research also uses the simple regressionmethod to Testing and processing of data. The results showed that customer satisfaction on product attributes benefit’s simPATI effect on customer loyalty by 48.6%Keywords: Customer Satisfaction, Product Attributes and Customer Loyalty.